2019
DOI: 10.3389/fimmu.2019.00307
|View full text |Cite
|
Sign up to set email alerts
|

Resolvin D2 Induces Resolution of Periapical Inflammation and Promotes Healing of Periapical Lesions in Rat Periapical Periodontitis

Abstract: Periapical periodontitis results from pulpal infection leading to pulpal necrosis and resorption of periapical bone. The current treatment is root canal therapy, which attempts to eliminate infection and necrotic tissue. But, in some cases periapical inflammation doesn't resolve even after treatment. Resolvins belongs to a large family of specialized pro-resolving lipid mediators that actively resolves inflammation signaling via specific receptors. Resolvin D2 (RvD2), a metabolite of docosahexaenoic acid (DHA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 71 publications
(105 reference statements)
2
45
0
Order By: Relevance
“…Based on these findings, it can be concluded that HMGB1 plays crucial roles not only in dental pulp inflammation, but also in dentine regeneration, enhancing DPC recruitment into the pulp injury, stimulating their differentiation into odontoblasts, and new dentin formation for healing of damaged tissues. Furthermore, we recently reported that RvD2 induces active resolution of inflammation through pulp-like tissue regeneration after root canal infection (80). It is possible that the HMGB1-C1q complex induces the production of RvD2 for dental pulp regeneration, as suggested by Liu et al (25).…”
Section: Dental Pulp Regenerationmentioning
confidence: 77%
“…Based on these findings, it can be concluded that HMGB1 plays crucial roles not only in dental pulp inflammation, but also in dentine regeneration, enhancing DPC recruitment into the pulp injury, stimulating their differentiation into odontoblasts, and new dentin formation for healing of damaged tissues. Furthermore, we recently reported that RvD2 induces active resolution of inflammation through pulp-like tissue regeneration after root canal infection (80). It is possible that the HMGB1-C1q complex induces the production of RvD2 for dental pulp regeneration, as suggested by Liu et al (25).…”
Section: Dental Pulp Regenerationmentioning
confidence: 77%
“…RvD2 has been shown to be defensive against Porphyromonas gingivalis-provoked periodontal bone loss, and to regulate the RANKL/OPG ratio (Mizraji et al 2018). More recently, Siddiqui et al (2019) demonstrated in rats that RvD2 reduces inflammatory cell infiltrate, periapical lesion size, and participates in the healing of periapical bone lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Although RvE1 and RvD2 have been widely explored in the resolution process in oral infection/inflammatory diseases, this is the first clinical study to investigate and quantify the levels of resolvins in periradicular tissue from teeth with primary endodontic infection and apical periodontitis and to assess the influence of intracanal medication on endogenous levels of RvE1 and RvD2. Up to now, in endodontics, there have only been two experimental model studies in rats that tested RvE1 and RvD2 as intracanal medications (Scarparo et al 2014, Siddiqui et al 2019. RvE1 intracanal medication demonstrated control of periapical inflammation in immature rat teeth with necrotic pulp (Scarparo et al 2014), whilst RvD2 intracanal medication induced healing of periapical lesions in rat periapical periodontitis (Siddiqui et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…24,25 Exogenous administration of SPMs has been shown in animal studies to dramatically aid in healing periapical lesions and reducing inflammation. [26][27][28][29] Periodontitis is generally caused by bacterial overgrowth, often Porphyromonas gingivalis, leading to biofilm formation and mucosal inflammation. An excessive immune response is believed to drive disease progression; and unresolved periodontitis and its resultant chronic inflammation can increase the risk for several diseases like atherosclerosis and Alzheimer's disease.…”
Section: Periodontitismentioning
confidence: 99%
“…27 The resolvin RvD2 also showed dramatic healing effects in rats with periodontitis, inducing calcification around the root and healing bone lesions. 29 In human periodontal ligament cells, LXA4 resolved inflammation through the TLR4/MyD88/NF-κB signaling pathway. 31 Patients suffering from localized aggressive periodontitis were shown to have increased leukotriene (proinflammatory) levels and significantly lower SPM levels, including LXA4, 15-hydroxyeicosatetraenoic acid (15-HETE), and 14-HDHA, than asymptomatic controls.…”
Section: Periodontitismentioning
confidence: 99%